Synchronous papillary renal neoplasm with reverse polarity and membranous nephropathy: a rare case report - Xing, Qingfei; Zhong, Minglei; Li, Xiaoxue; Cao, Tingshuai; Liu, Xiaoteng; Wang, Fangfei; He, Li (Frontiers in Oncology, 2025)
BackgroundPapillary renal neoplasm with reverse polarity (PRNRP) is a relatively rare subtype of papillary renal cell carcinoma (PRCC) and is considered to be a tumor of low malignant potential. Membranous nephropathy (MN) is frequently associated with malignant tumors but rarely accompanies renal cell carcinoma. Synchronous papillary renal neoplasm with reverse polarity and membranous nephropathy has not been reported in the current study. (We searched in PubMed, Web of Science databases, Embase, and Medline in the English language from 1970 to October 2024. The keywords used were “papillary renal neoplasm with reverse polarity” and “membranous nephropathy”.)Case presentationA 66-year-old man was admitted to the hospital with lower extremity edema and hypertension and presented with nephrotic syndrome including hypoalbuminemia and proteinuria. Enhanced CT scan showed a 3.7*3.0 cm round-like soft tissue density foci at the lower pole of the left kidney, with obvious inhomogeneous enhancement. The patient underwent a laparoscopic partial nephrectomy of the left kidney. Histologic and immunohistochemical results showed typical features of PRNRP, including a papillary structure covered by a single layer of cuboidal cells with finely grained eosinophilic cytoplasm, nuclei that were mostly regular and apically located, and GATA3 (+). The biopsy of pericarcinoma tissue showed membranous nephropathy and glomerular segmental sclerosis. The patient’s nephrotic syndrome resolved and the tumor did not recur or metastasize during 22 months of postoperative follow-up.ConclusionWe reported a case of synchronous papillary renal neoplasm with reverse polarity with membranous nephropathy. The mechanism of renal tumor-associated nephrotic syndrome is unclear and more medical records are needed for research.